Monomeric C‐reactive protein and inflammation in age‐related macular degeneration. Issue 2 (19th September 2016) - Chirco, Kathleen R; Whitmore, S Scott; Wang, Kai; Potempa, Lawrence A; Halder, Jennifer A; Stone, Edwin M; Tucker, Budd A; Mullins, Robert F
Abstract: Age‐related macular degeneration (AMD) is a devastating disease characterized by central vision loss in elderly individuals. Previous studies have suggested a link between elevated levels of total C‐reactive protein (CRP) in the choroid, CFH genotype, and AMD status; however, the structural form of CRP present in the choroid, its relationship to CFH genotype, and its functional consequences have not been assessed. In this report, we studied genotyped human donor eyes ( n = 60) and found that eyes homozygous for the high‐risk CFH (Y402H) allele had elevated monomeric CRP (mCRP) within the choriocapillaris and Bruch's membrane, compared to those with the low‐risk genotype. Treatment of choroidal endothelial cells in vitro with mCRP increased migration rate and monolayer permeability compared to treatment with pentameric CRP (pCRP) or medium alone. Organ cultures treated with mCRP exhibited dramatically altered expression of inflammatory genes as assessed by RNA sequencing, including ICAM‐1 and CA4, both of which were confirmed at the protein level. Our data indicate that mCRP is the more abundant form of CRP in human choroid, and that mCRP levels are elevated in individuals with the high‐risk CFH genotype. Moreover, pro‐inflammatory mCRP significantly affects endothelial cell phenotypes in vitro and ex vivo, suggesting a role for mCRP in choroidal vascular dysfunction in AMD. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.